EVALUASI PENGEMBANGAN EKONOMI NELAYAN PENERIMA PROGRAM BANTUAN LANGSUNG MASYARAKAT PENGEMBANGAN USAHA MINA PERDESAAN (BLM-PUMP) DI KELURAHAN TIDORE - Venancia ., Maengkom; Leonardus R. Rengkung; Agnes E. Loho (AGRI-SOSIOEKONOMI, 2015)
The aims of this researcxh are to evaluate and assess the effectiveness of Bantuan Langsung Masyarakat – Pengembangan Usaha Mina Perdesaan (BLM-PUMP) program, and to know the impact of the implementation of the program to the fishing communities’ economic life in Tidore Village, Sub-district of East Tahuna. The village is one of the target area of the BLM - PUMP program. Research carried out for three months; with the number of respondents sample are 17 fishermen. Data were analyzed by descriptive qualitative and quantitative in tabulation form, percentage and scoring. The results showed that the BLM-PUMP program in Tidore Village accordance with the procedures and criteria set by the government. There are some deficiencies found in the implementation of the program: a) non-physical aid program forms is not used optimally; b) there is no capital turnover; c) supervisor does not properly function, assisting and training does not continue on to post-disbursement.  BLM-PUMP program has produced output in the form of fishing infrastructure that is still used as a shared/KUB asset, and the Joint Business Group (KUB), but the function did not go well. BLM-PUMP program in the Village Tidore founded to be less effective, because the program objectives are not fully achieved. Distribution of BLM-PUMP only able to increase the income of fishermen, and foster entrepreneurial fishermen sufficiently, but are not able to improve the function of KUB institutional as a financial institution partners for fishermen. Nonetheless, the program provides economic impacts on fishing communities, which increase the income of fishermen and sufficiently reduce the dependence of fishermen on the capital providers/owners. (individual / institution).